The association between serum 25‐hydroxyvitamin D and the prevalence of herpes simplex virus. Issue 1 (18th November 2022) - Huang, Jiaofeng; Wu, Yinlian; Wang, Mingfang; Lin, Su
Abstract: Previous studies have reported a potential anti‐infection effect for vitamin D. However, the relationship between vitamin D status and herpes simplex virus (HSV) infection has not yet been evaluated. Therefore, this study aimed to determine the association between serum 25‐hydroxyvitamin D [25(OH)D] and infection with HSV types 1 and 2 (HSV‐1 and HSV‐2). Data were collected from the National Health and Nutrition Examination Survey from 2007 to 2016. The association between 25(OH)D and HSV prevalence was evaluated using propensity score matching (PSM) and univariate and multivariate logistic regression analyses. Overall, 14 174 participants were included in the final analysis. Before PSM, 8639 (60.9%) had positive HSV‐1 and 2636 (18.6%) had HSV‐2. The HSV‐1 and HSV‐2 positive groups had more females and older individuals ( p  < 0.05). The HSV‐2 patients had lower 25(OH)D levels than those with HSV‐1. Age and gender did not differ in the groups after PSM ( p  > 0.05). The 25(OH)D level was significantly lower in the HSV‐1 and HSV‐2 groups than in the non‐HSV infection groups. Multivariate logistic regression showed that serum 25(OH)D level was negatively associated with HSV‐1 and HSV‐2 infection (odds ratio [OR] = 0.730 and 0.691, p  < 0.001, respectively). Vitamin D deficiency was an independent risk factor for both HSV‐1 and HSV‐2 (adjusted OR = 2.205 and 2.704, p  < 0.001, respectively). Lower serum 25(OH)D levels correlated significantly with increased HSV‐1 and HSV‐2 infection risk.